Model of Free Grading to Guess Cell Probability in Incomplete Contingency Table - Dewi, Yuliani Setia (Majalah Ilmiah Matematika dan Statistika, 2016)
The problem of estimating cell probabilities from incomplete tables, that is when either the row or column variable missing for some of the subjects is very common. This article describes Lattice Conditional Independence Model to estimate cell probabilities in incomplete contingency table.